Technology-Enhanced Arabic Listening Instruction and Its Learning Challenges: A Qualitative Study of Undergraduate Students - Achmad Muzammil; Nuril Mufidah (https://unikhams.ac.id/, 2026)
Technology-enhanced instruction has expanded opportunities for Arabic listening practice through authentic audiovisual materials, repeated exposure, collaborative learning, and digital assessment; however, students may continue to experience difficulties when technological resources are not aligned with their linguistic and cognitive readiness. This study aimed to analyze the implementation of technology-enhanced Arabic listening instruction and identify the linguistic, phonological, technical, cognitive, and affective challenges experienced by undergraduate students in an Arabic Language Education program. A descriptive qualitative design was employed in Class C at Maulana Malik Ibrahim State Islamic University of Malang. Data were collected through classroom observations, semi-structured interviews with students and the course lecturer, and analysis of instructional documents, including learning materials, video links, and assessment records. The data were analyzed through condensation, coding, categorization, thematic development, data display, and conclusion verification. The findings showed that listening instruction was organized through pre-class YouTube exposure, group presentations, classroom discussions, question-and-answer activities, and Quizizz-based formative assessment. Despite this structured integration, students encountered limited vocabulary, difficulty distinguishing Arabic phonemes with similar places of articulation, rapid native-speaker speech, dialect variation, unclear word boundaries, poor audio quality, anxiety, boredom, and reduced concentration. These challenges interacted and frequently disrupted students’ ability to process spoken Arabic continuously and construct coherent meaning. The study concludes that digital technology alone is insufficient to improve Arabic listening proficiency. Effective instruction requires graded listening materials, explicit phonological training, vocabulary preparation, reliable audio resources, supportive classroom interaction, and diagnostic assessment aligned with learners’ actual proficiency.